Control-style choices and performance impacts: How should senior IS managers enact control over uncertain IS projects? - Wiener, Martin; Cram, W. Alec; Remus, Ulrich; Mähring, Magnus (Decision Support Systems, 2023)
Information systems (IS) projects are notoriously difficult to control, especially under conditions of uncertainty. This difficulty is particularly pronounced for senior IS managers, such as CIOs and IT Vice Presidents, who tend to have scarce time and limited project-related knowledge but are ultimately held accountable for IS project performance. Focusing on this under-researched controller category, the study at hand contributes new insights into the enactment of controls by exploring how IS project uncertainty affects senior IS managers' control-style choices, as well as how it moderates the impact of such choices on process and product performance. Based on a survey of 150 senior IS managers, we find that IS project uncertainty increases managers' use of an authoritative control style but is unrelated to their use of an enabling control style. Further, in IS projects characterized by uncertainty, an authoritative control style is found to be effective for process performance, whereas an enabling style is found to be effective for product performance. Moreover, the results of a post-hoc analysis show that using the two control styles simultaneously under uncertainty delivers no discernible benefits, suggesting a decision-related control dilemma. Theoretical and practical implications are discussed. •Study focuses on under-researched controller category; namely, senior IS managers.•It extends existing theory to account for (novelty-induced) IS project uncertainty.•Senior IS managers prefer authoritative control style in uncertain IS projects.•Authoritative (enabling) control style improves only process (product) performance.•Combination of two control styles delivers no discernible performance benefits.